Contribution to the knowledge of the bryophyte flora of Ecuador - Schäfer-Verwimp, A.; Lehnert, M.; Nebel, M. (Phytotaxa, 2013)
Fifty species, one subspecies and one variety of liverworts, as well as three species and one variety of mosses are newly reported for the bryophyte flora of Ecuador, based on extensive fieldwork in 2011 and 2012. 371 new province records of liverworts and 5 of hornworts are increasing the number of liverwort and hornwort state records from 1744 to 2120.